A vegetation survey of Sumatran orangutan habitat was carried out as part of a larger orangutan conservation project in Batang Toru forest during October 2007–January 2008. The purpose was to provide information about the forest structure and composition including orangutan feeding and nesting trees based on 3.84 ha total cumulative area sampling in 11 sites. The results of the inventory of trees with diameter at breast height (DBH) of 96 plots 20x20 m size e” 10 cm in 3.84 ha area sampling show - Roland H. Simorangkir; Sri Supraptini Mansjoer; M. Bismark (Pusat Studi Satwa Primata LPPM-IPB, 2009)
A vegetation survey of Sumatran orangutan habitat was carried out as part of a larger orangutan conservation project in Batang Toru forest during October 2007–January 2008. The purpose was to provide information about the forest structure and composition including orangutan feeding and nesting trees based on 3.84 ha total cumulative area sampling in 11 sites. The results of the inventory of trees with diameter at breast height (DBH) of 96 plots 20x20 m size e” 10 cm in 3.84 ha area sampling showed that 274 trees species in 56 families, represented by 1,896 trees with a total basal area of 148.9 m2/ha and density of 494 trees/ha, totally the forest habitat dominated by Sapotaceae, Fagaceae, Dipterocarpaceae, Myrtaceae, Anacardiaceae, Casuarinaceae, Podocarpaceae, Lauraceae, Euphorbiaceae, and Theaceae. The forest structure and composition were dominated by trees with diameters of 10-30 cm (75.6% of total inventoried trees) and heights of 10-30 m (80.4%). There were 96 orangutan feeding trees species in 25 families, represented by 536 trees with total basal area of 46.7 m2/ha. The most prominent feeding trees species were Madhuca sp. (local name: sapot), Lithocarpus conocarpa (hoteng), Castanopsis sp. (andihit), Podocarpus imbricatus (sampinur bunga), Litsea firma (urat tiga), Ganua motleyana (sapot), and Garcinia bancana (hole tanduk). The feeding trees with diameters 10-30 cm (77.4% of total identified feeding trees) and heights 10-30 m (78.5%) distributed abundantly in Batang Toru forest, especially in the old moist secondary forests. Key words: Sumatran orangutan, habitat, vegetation survey, Batang Toru forest